2022
DOI: 10.1155/2022/9441357
|View full text |Cite|
|
Sign up to set email alerts
|

A Versatile and Ubiquitous IoT-Based Smart Metabolic and Immune Monitoring System

Abstract: In the present medical age, the focus on prevention and prediction is achieved using the medical internet of things. With a broad and complete framework, effective behavioral, environmental, and physiological criteria are necessary to govern the major healthcare sectors. Wearables play an essential role in personal health monitoring data measurement and processing. We wish to design a variable and flexible frame for broad parameter monitoring in accordance with the convenient mode of wearability. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Researchers are striving to enhance the safety and effectiveness of driverless technologies to operate in complex, dynamic environments. During the recent decade, IoT has been increasingly adopted in personal and public health [2,3], home [4], agriculture and forestry [5][6][7], climate and meteorological studies [8], among others. In Section 3, we will briefly discuss IoT applications grouped into seven different categories of IoT systems.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are striving to enhance the safety and effectiveness of driverless technologies to operate in complex, dynamic environments. During the recent decade, IoT has been increasingly adopted in personal and public health [2,3], home [4], agriculture and forestry [5][6][7], climate and meteorological studies [8], among others. In Section 3, we will briefly discuss IoT applications grouped into seven different categories of IoT systems.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%